2016
DOI: 10.1007/s12105-015-0678-1
|View full text |Cite
|
Sign up to set email alerts
|

Phosphaturic Mesenchymal Tumor Involving the Head and Neck: A Report of Five Cases with FGFR1 Fluorescence In Situ Hybridization Analysis

Abstract: Phosphaturic mesenchymal tumor (PMT) is a rare neoplasm; however, it is the most common cause of tumor-induced osteomalacia (TIO), a paraneoplastic syndrome characterized by renal phosphate wasting and hypophosphatemia. A subset of PMTs harbours an FGFR1 translocation although this alteration has not been demonstrated in PMT involving a head and neck site. We present a series of five PMTs involving the head and neck and demonstrate the diagnostic utility of fluorescence in situ hybridization (FISH) for detecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 14 publications
0
22
0
1
Order By: Relevance
“…The PLAG1 and HMGA2 rearrangement status of 27 tumors was previously determined and reported . Fibroblast growth factor receptor 1 ( FGFR1 ) FISH was performed as previously described …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The PLAG1 and HMGA2 rearrangement status of 27 tumors was previously determined and reported . Fibroblast growth factor receptor 1 ( FGFR1 ) FISH was performed as previously described …”
Section: Methodsmentioning
confidence: 99%
“…7 Fibroblast growth factor receptor 1 (FGFR1) FISH was performed as previously described. 23 Library Preparation, Sequencing, and Data Analysis DNA extraction and targeted next-generation sequencing analysis were performed as previously described. 19 Library concentrations and amplicon sizes were determined using the TapeStation System (Agilent Technologies, Santa Clara, Calif).…”
Section: Immunohistochemistrymentioning
confidence: 99%
“…The cause of oncogenic osteomalacia is usually benign mesenchymal or mixed connective tissue tumors (1) or, rarely, malignant mesenchymal tumors (2). Recently, FGFR1 translocation has been described in a fraction of phosphaturic mesenchymal tumors of the head and neck (1). A substantial number of these tumors demonstrate somatostatin receptor expression, and 68 Ga-DOTATATE PET/CT has evolved as an important imaging modality to locate the causative tumors (3).…”
mentioning
confidence: 99%
“…A total of 4 cases (57.14%) had recurrence during the follow-up. [6,9,10] In our study, the biochemical indicators of case 1 showed no abnormities which made diagnosis di cult.…”
Section: Discussionmentioning
confidence: 54%